Run equilibria in a model of financial intermediation - Huberto M. Ennis; Todd Keister (Federal Reserve Bank of New York, 2008)
We study the Green and Lin (2003) model of financial intermediation with two new features: traders may face a cost of contacting the intermediary, and consumption needs may be correlated across traders. We show that each feature is capable of generating an equilibrium in which some (but not all) traders 'run' on the intermediary by withdrawing their funds at the first opportunity regardless of their true consumption needs. Our results also provide some insight into elements of the economic environment that are necessary for a run equilibrium to exist in general models of financial intermediation. In particular, our findings highlight the importance of information frictions that cause the intermediary and traders to have different beliefs, in equilibrium, about the consumption needs of traders who have yet to contact the intermediary.
Keywords: D82; D84; G21; 330; Bank runs; optimal contracts; private information; incentive feasibility; self-fulfilling expectations; Finanzintermediär; Allokationseffizienz; Bankenkrise; Theorie